Coexisting spin and Rabi oscillations at intermediate time regimes in electron transport through a photon cavity - Gudmundsson, Vidar; Gestsson, Hallmann; Abdullah, Nzar Rauf; Tang, Chi-Shung; Manolescu, Andrei; Moldoveanu, Valeriu (Beilstein Journal of Nanotechnology, 2019)
In this work, we theoretically model the time-dependent transport through an asymmetric double quantum dot etched in a two-dimensional wire embedded in a far-infrared (FIR) photon cavity. For the transient and the intermediate time regimes, the current and the average photon number are calculated by solving a Markovian master equation in the dressed-states picture, with the Coulomb interaction also taken into account. We predict that in the presence of a transverse magnetic field the interdot Rabi oscillations appearing in the intermediate and transient regime coexist with slower non-equilibrium fluctuations in the occupation of states for opposite spin orientation. The interdot Rabi oscillation induces charge oscillations across the system and a phase difference between the transient source and drain currents. We point out a difference between the steady-state correlation functions in the Coulomb blocking and the photon-assisted transport regimes.
Keywords: electron transport; interactions; photon cavity; photon-dressed electron states; time dependent